2017
DOI: 10.1536/ihj.17-264
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Exercise Test

Abstract: SummaryThe cardiopulmonary exercise test (CPX) is an essential examination for detecting pathophysiological derangement and determining treatment policy because it clarifies not only the changes of hemodynamics but also abnormality in the whole body during exercise where heart disease patients often feel symptoms.To utilize CPX effectively, we must understand each parameter, such as peak oxygen uptake (peak !O2), peak !O2/HR, and !E/ !CO2. In addition, comparison of each parameter, for example, peak !O2 and !E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 28 publications
2
43
0
2
Order By: Relevance
“…ability in patients with CHF and was found to be related to prognosis. 35,36) Compared with the standard anti-heart failure therapy, the added ivabradine treatment led to a significantly lower VE/VCO2 (MD = −2.68, 95% CI −4.81 to −0.55, P = 0.01) in patients with CHF ( Figure 2E). Furthermore, the analysis of the peak VO2 demonstrated that the high heterogeneity might be associated with the different follow-up times of the included studies.…”
Section: Improved Cardiopulmonary Functionmentioning
confidence: 99%
“…ability in patients with CHF and was found to be related to prognosis. 35,36) Compared with the standard anti-heart failure therapy, the added ivabradine treatment led to a significantly lower VE/VCO2 (MD = −2.68, 95% CI −4.81 to −0.55, P = 0.01) in patients with CHF ( Figure 2E). Furthermore, the analysis of the peak VO2 demonstrated that the high heterogeneity might be associated with the different follow-up times of the included studies.…”
Section: Improved Cardiopulmonary Functionmentioning
confidence: 99%
“…41) These changes relate to a decrease in sympathovagal activity to the heart. 49,50) In this study, no difference in physical performance measures was observed. Furthermore, the three groups had similar maximum oxygen consumption and resting heart rate.…”
Section: Discussionmentioning
confidence: 47%
“…The sensitivity of respiratory chemo-receptors increases when the sympathetic nerve is activated and/oracidosis occurs. These conditions often occur in HF patients [43] . These subjects experience shortness of breath throughout mild to vigorous activity.…”
Section: Discussionmentioning
confidence: 99%